the influence of concentration and motivation on the accuracy of the slingshot game - Putri, Danti; Danti Putri; Yudha Kusuma , Donny Wira; Wahyudi, Agung (Universitas Negeri Semarang, 2024)
Slingshot games are games that don't use much physical activity but require fine motor skills in playing and doing activities. The slingshot game requires patience, concentration, motivation, mental endurance and high anxiety, this is done to obtain proper accuracy. The aim of this research is to determine the influence of concentration and motivation on the accuracy of the slingshot game. This research is quantitative research with a correlational descriptive method. Data collection techniques use observation, questionnaires, tests and documentation. This research was carried out in 6 public elementary schools in Semarang Regency. The sample in this study consisted of 125 students, divided into 51 male students and 74 female students. The data analysis techniques used in this research used normality tests, linearity tests, homogeneity tests, and hypothesis tests. The research results show that concentration and motivation when aiming at the target greatly influence the results of shots on target. The conclusion of this research is that the results show a significance value of 0.000 which is smaller than 0.05, which means that concentration and motivation have a positive and significant influence on the accuracy of the slingshot game, with an R Square value of 51.2%, while 48.8% is influenced by variables other.